2021
DOI: 10.3390/su13116219
|View full text |Cite
|
Sign up to set email alerts
|

Determinants That Influence Green Product Purchase Intention and Behavior: A Literature Review and Guiding Framework

Abstract: Environmental deterioration brought about by consumers’ non-feasible utilization pattern is putting a pressure on the environment and is obstructing sustainable development. To hinder this impact and stimulate a more sustainable economic growth, one solution is to lessen or move utilization patterns from conventional products to eco-friendly products. The authors conducted a review study of green purchase behavioral research across the 6-year period from 2015 to 2021, identifying 108 studies that met our inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
93
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(100 citation statements)
references
References 169 publications
(124 reference statements)
4
93
0
3
Order By: Relevance
“…Although the correlations were weak or modest at best, our results build on previous findings [21,23,[25][26][27][28][34][35][36] and show that knowledge, attitudes toward the environment and bio-based ingredients, past green purchasing behavior, and intention to buy green and lignin skincare are all positively related. However, contrary to our predictions, health consciousness had the weakest associations with sustainable purchasing behavior and intention to purchase and a non-significant relationship with knowledge and willingness to buy lignin-based sunscreens, suggesting that consumers may not perceive lignin-based sunscreens and other bio-based skincare products as healthier choices for them [31,32].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Although the correlations were weak or modest at best, our results build on previous findings [21,23,[25][26][27][28][34][35][36] and show that knowledge, attitudes toward the environment and bio-based ingredients, past green purchasing behavior, and intention to buy green and lignin skincare are all positively related. However, contrary to our predictions, health consciousness had the weakest associations with sustainable purchasing behavior and intention to purchase and a non-significant relationship with knowledge and willingness to buy lignin-based sunscreens, suggesting that consumers may not perceive lignin-based sunscreens and other bio-based skincare products as healthier choices for them [31,32].…”
Section: Discussionsupporting
confidence: 84%
“…Health consciousness, which represents a person's awareness, concern, and willingness to do something about one's health [20], has also begun to attract attention as a potential determinant of greener consumption [21], as people perceive organic products as a healthier choice [22]. For instance, research has shown that people who are more conscious about both the environment and their own health are likelier to have a more positive attitude and purchase eco-friendly, organic, and self-protective products [23][24][25][26][27][28]. Literature focusing on green cosmetics and skincare products in particular shows similar results; concerns about the environment and human health predicted a more positive attitude towards green skincare, which in turn predicted purchase intention [21,29,30].…”
Section: Attitude Knowledge and Behavior In Relation To Green Skincare Productsmentioning
confidence: 99%
“…Litvine and Wüstenhagen analyzed the behavioral factors directly influencing green purchases and highlighted that the role of willingness to pay is a major factor directly affecting green behavior [60]. Moreover, perceived simplicity and benefit certainty indirectly affect behavior by mediating intentions [61]. Barbarossa and Pastore considered that in a marketplace setting, green consumers tend to be more conscious of the price, quality, and lack of availability of green products [62].…”
Section: Discussionmentioning
confidence: 99%
“…Hasil temuan beberapa kajian sebelumnya menunjukkan bahwa terdapat beberapa aspek yang menentukan pergeseran pola konsumsi individu maupun masyarakat. Pergeseran pola konsumsi tersebut ditentukan oleh tujuan membeli produk (Wang & Chao, 2020;Eisend & Hermann, 2020), kemasan produk yang menarik (Chen et al, 2017;Wijekoon & Sabri, 2021), penampilan dan reputasi (Bilro & Loureiro, 2020), berdasarkan biaya dan bukan berdasarkan manfaat atau kegunaan (Bukhari et al, 2020), status sosial (Boström, 2020), dan kepercayaan diri (White et al, 2019;Pang et al, 2021).…”
Section: Gambar 1 Pertumbuhan Pdrb Provinsi Sulawesi Selatan Menurut Pengeluaranunclassified